Global health equity in United Kingdom university research: a landscape of current policies and practices. Issue 1 (December 2016) - Gotham, Dzintars; Meldrum, Jonathan; Nageshwaran, Vaitehi; Counts, Christopher; Kumari, Nina; Martin, Manuel; Beattie, Ben; Post, Nathan
Abstract Background Universities are significant contributors to research and technologies in health; however, the health needs of the world's poor are historically neglected in research. Medical discoveries are frequently licensed exclusively to one producer, allowing a monopoly and inequitable pricing. Similarly, research is often published in ways that make it inaccessible. Universities can adopt policies and practices to overcome neglect and ensure equitable access to research and its products. Methods For 25 United Kingdom universities, data on health research funding were extracted from the top five United Kingdom funders' databases and coded as research on neglected diseases (NDs) and/or health in low- and lower-middle-income countries (hLLMIC). Data on intellectual property licensing policies and practices and open-access policies were obtained from publicly available sources and by direct contact with universities. Proportions of research articles published as open-access were extracted from PubMed and PubMed Central. Results Across United Kingdom universities, the median proportion of 2011–2014 health research funds attributable to ND research was 2.6% and for hLLMIC it was 1.7%. Overall, 79% of all ND funding and 74% of hLLMIC funding were granted to the top four institutions within each category. Seven institutions had policies to ensure that technologies developed from their research are affordable globally. Mostly, universities licensed their inventions to third parties in a way that confers monopoly rights. Fifteen institutions had an institutional open-access publishing policy; three had an institutional open-access publishing fund. The proportion of health-related articles with full-text versions freely available online ranged from 58% to 100% across universities (2012–2013); 23% of articles also had a creative commons CC-BY license. Conclusion There is wide variation in the amount of global health research undertaken by United Kingdom universities, with a large proportion of total research funding awarded to a few institutions. To meet a level of research commitment in line with the global burden of disease, most universities should seek to expand their research activity. Most universities do not license their intellectual property in a way that is likely to encourage access in resource-poor settings, and lack policies to do so. The majority of recent research publications are published open-access, but not as gold standard (CC-BY) open-access.